USE OF TOPONYMS IN MODERN FRENCH MEDIA - Azamjonova, Sarvinoz (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The article deals with the role of toponyms in the media in France and the figure of speech used in media texts to influence the reader or listener. The official and unofficial toponyms are considered